2009
DOI: 10.1186/1743-0003-6-14
|View full text |Cite
|
Sign up to set email alerts
|

A binary method for simple and accurate two-dimensional cursor control from EEG with minimal subject training

Abstract: Background: Brain-computer interfaces (BCI) use electroencephalography (EEG) to interpret user intention and control an output device accordingly. We describe a novel BCI method to use a signal from five EEG channels (comprising one primary channel with four additional channels used to calculate its Laplacian derivation) to provide two-dimensional (2-D) control of a cursor on a computer screen, with simple threshold-based binary classification of band power readings taken over pre-defined time windows during s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 26 publications
0
30
0
Order By: Relevance
“…We found that the discrimination of ERD from ERS was much more reliable than the discrimination of ERD from background activities in conventional BCI methods (Bai et al, 2008;Kayagil et al, 2009). A short-lasting burst of EEG oscillation, termed as beta rebound or beta-ERS, has been observed in beta band (16-30 Hz) over human sensorimotor area after subjects produce a self-paced movement (Salmelin et al, 1995;Pfurtscheller and Lopes da Silva, 1999;Neuper and Pfurtscheller, 2001).…”
Section: What Challenges Practical Applications Of Eeg-bci?mentioning
confidence: 93%
See 1 more Smart Citation
“…We found that the discrimination of ERD from ERS was much more reliable than the discrimination of ERD from background activities in conventional BCI methods (Bai et al, 2008;Kayagil et al, 2009). A short-lasting burst of EEG oscillation, termed as beta rebound or beta-ERS, has been observed in beta band (16-30 Hz) over human sensorimotor area after subjects produce a self-paced movement (Salmelin et al, 1995;Pfurtscheller and Lopes da Silva, 1999;Neuper and Pfurtscheller, 2001).…”
Section: What Challenges Practical Applications Of Eeg-bci?mentioning
confidence: 93%
“…After an inter-trial interval randomly from 4 to 6 s, the next text message was provided. The detailed paradigm was provided in a previous study (Bai et al, 2008;Kayagil et al, 2009). Patients participated in both motor execution and motor imagery sessions.…”
Section: Binary and Four-directional Control Paradigms For 2d Controlmentioning
confidence: 99%
“…The acquisition and maintenance of BCI-based skills like reliable multidimensional movement control require comparable plasticity (eg, as described by various investigators 10,24,110,113 ). Brain-computer interface operation rests on the effective interaction of 2 adaptive controllers, the CNS and the BCI.…”
Section: Reliabilitymentioning
confidence: 99%
“…The output might be used to operate a spelling program on a computer screen through letter selection [6, 11], to move a cursor on a computer screen [12, 84, 85], to drive a wheelchair [86, 87] or other assistive devices [88], to manipulate a robotic arm [89, 90], or even to control movement of a paralyzed arm through a neuroprosthesis [15, 91]. At present, the most commonly used output device is the computer screen, and it is used for communication.…”
Section: Bci Definition Signal Types and Operationmentioning
confidence: 99%